2015
DOI: 10.1039/c4ra16696e
|View full text |Cite
|
Sign up to set email alerts
|

Elastomeric microfluidic valve with low, constant opening threshold pressure

Abstract: This paper presents the realization of low, constant opening threshold pressures of an elastomeric valve by appropriate design and surface coating of the valve in a self-oscillating microfluidic device. The valve has a V-shaped valve seat, which separates the valve's inlet and outlet, and a membrane-pressurization bottom chamber. We utilized the V-shaped valve seat design to manipulate the mechanical deformation of the valve's membrane due to differences in applied pressure. Furthermore, we used a simple biomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…During this process, biomolecules in the solution bound on the valve surfaces and reduced the adhesive property of PDMS, thereby decreasing the opening threshold pressure of the microfluidic valves. Additional details on the microfabrication process are provided in the supporting information of .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, biomolecules in the solution bound on the valve surfaces and reduced the adhesive property of PDMS, thereby decreasing the opening threshold pressure of the microfluidic valves. Additional details on the microfabrication process are provided in the supporting information of .…”
Section: Methodsmentioning
confidence: 99%
“…Although dynamic controllers enable versatile regulation of chips, installing and operating the controllers are relatively costly and require expertise in electromechanics. This drawback is the motivation for the birth of instruction‐embedded microfluidic devices that mimic the operation of electronic circuits .…”
Section: Introductionmentioning
confidence: 99%
“…The continuous regulation of the valve can be controlled with the manipulation of airflow, here pressure on chip, so that the external pressure is constant. [ 61 ]…”
Section: Microfluidic Setups For Dynamically Controlled Environments mentioning
confidence: 99%
“…The constant flow rate of this microvalve was 0.83 mL/min. Jaemin et al [ 21 ] performed an experimental analysis on different shaped structures in normally closed microvalve models. The study found that the microvalve can achieve a near-low constant opening threshold pressure regardless of the change in the input flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the microvalve can achieve a near-low constant opening threshold pressure regardless of the change in the input flow rate. Later, Natarajan et al [ 22 ] performed the FSI analysis on two different models (taking from [ 21 ]) in normally closed microvalve models. The characteristics of fluid flow and the behavior of membrane deformation inside the normally closed microvalve were observed.…”
Section: Introductionmentioning
confidence: 99%